Tinjauan Yuridis Hukuman Mati terhadap Pelaku Pencabulan pada Anak di Bawah Umur dalam Perspektif HAM - Ngadio, Gabriel; Firmansyah, Hery (Universitas Ekasakti, 2023)
Indonesia is a legal state which consists of various rules to provide protection, security and welfare for its people. Especially regarding the rights of every person, such as the rights that every person gets when he is in his parents' womb, namely Human Rights, but not throughout a person's life it is guaranteed that his rights will not be disturbed or injured by other people, such as cases of sexual harassment received by children, both boys and girls. This research uses a normative type of research. In Indonesian law there are regulations that regulate the death penalty for perpetrators of abuse or rape of children. There are various pros and cons to this regulation because the imposition of the death penalty sanction is also a violation of a person's right to life which is regulated in Human Rights.